Permodelan Bangkitan Pergerakan untuk Beberapa Tipe Perumahan di Pekanbaru - Parada Afkiki Eko Saputra (Universitas Quality, 2018)
The trip generation existence from a housing resident in Pekanbaru City could influence a road service level. It needed a study on trip generation from a housing resident. So that next to develop a new resident complex or in the future, it could be identified how big its influence towards road network capacity in Pakanbaru City. Factors that influenced a trip generation were: move behavior from each housing, trip number yielded, and figuring out other factors that influenced a trip event. Parameter used in a trip generation model make was a Multiple Linear Regression Analysis. Data was taken based on a housing resident trend to make a trip that was explained in some variables such as: family member number (X1), family income level (X2), car ownership (X3), motorbike ownership number (X4), working family members (X5), schooling family members (X6), occupation (X7), family head age (X8), and building width (X9). An analysis result showed that the best model could be applied in a housing location planning today was a multiple linear regression model equation in a luxurious housing type namely Y1 = 3.062 + 1.323 X1 + 0.175 X4 + 0.526 X6 due to the formed equation had been able to represent variables affected towards a move emergence from housing.